Nanoparticles in Food Industry - Ibrahim Ali , Noorbatcha (2015)
The recent surge in the advancement of nanotechnology related techniques has opened new vistas in the applications of nanoparticles in food and agricultural industry. In food industry, nanoparticles has the potential to be used in food packaging, preservations, retain the flavor, fragrance release, enhance the appearance, smart delivery, separations and purifications. There are several food items containing nanoparticles already in the market. According to one market survey, the value of global food encapsulation market is expected to grow at a rate of 6.1% per year reaching a value of $39.5 billion by the year 2020.